2022
DOI: 10.1037/dev0001239
|View full text |Cite
|
Sign up to set email alerts
|

Children’s intentional switching of auditory selective attention in spatial and noisy acoustic environments in comparison to adults.

Abstract: am MainChildren's development and education take place in educational buildings with highly complex acoustic scenes, including spatially distributed target speakers, many surrounding distracting sounds, and general background noises. Auditory selective attention, therefore, is a valuable tool to orient oneself, to focus on specific sound sources, and to extract relevant information. Until now, it is unknown to what extent children have developed the cognitive processes of intentional attention control in spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 34 publications
4
12
0
Order By: Relevance
“…To investigate the switching of auditory selective attention in children, as well as the related developmental effects, the paradigm by Oberem et al [ 12 ] was adapted for children by Loh et al [ 18 ]. To be understandable for young children, the task was changed slightly.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…To investigate the switching of auditory selective attention in children, as well as the related developmental effects, the paradigm by Oberem et al [ 12 ] was adapted for children by Loh et al [ 18 ]. To be understandable for young children, the task was changed slightly.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the visual cue and the feedback elements presented on a computer display, no visual stimuli were used. The child-appropriate paradigm was validated with 24 children at the ages of 6–10 years, as well as 24 young adults in conditions with and without noise [ 18 ]. The first results indicated that children are more susceptible to noise than adults, which was reflected in higher error rates and lower reaction times.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, their HRTFs differ from adult or standardized artificial heads [ 33 ] HRTFs based on adult geometries. Nonetheless, the same artificial head HRTFs are used in virtual environments for children (e.g., [ 34 , 35 , 36 ]). Kids under the age of 10 are especially of interest here, as the growth-rate of the pinnae significantly decreases around that age [ 31 ].…”
Section: Introductionmentioning
confidence: 99%